Development of a Computational Thinking-Based Learning Module Aligned with the Merdeka Curriculum for Primary - Tahsin, Muhammad (International Journal Education and Computer Studies (IJECS), 2024)
This study aims to develop a computational thinking learning module tailored to the Merdeka Curriculum for primary school students. The Merdeka Curriculum, which emphasizes 21st-century skills, provides a flexible and adaptive framework for education; however, integrating computational thinking remains a challenge in many schools. Through a research and development (R&D) approach, this study identifies the needs, designs, and tests an innovative learning module. The development process begins with a needs analysis conducted through surveys and interviews with teachers and students in primary schools implementing the Merdeka Curriculum. Based on these findings, the learning module is designed to include various interactive activities and exercises aimed at developing computational thinking skills in children. The module is then validated by educational experts and piloted in several primary schools. The trial results indicate that the developed learning module is effective in enhancing students' understanding of computational thinking concepts. Feedback from teachers and students also suggests that the module is engaging, easy to understand, and supports active learning in the classroom. Nevertheless, challenges such as limited time and school facilities need to be addressed for broader implementation. This study makes a significant contribution by providing educational resources that support the development of computational thinking skills in primary schools, in line with the principles of the Merdeka Curriculum. Recommendations for further research and field implementation are also presented to strengthen the outcomes obtained.